2017
DOI: 10.1088/1361-648x/aa7707
|View full text |Cite
|
Sign up to set email alerts
|

Orbital electronic occupation effect on metal–insulator transition in Ti x V1−x O2

Abstract: A series of Ti V O (0%  ⩽  x  ⩽  4.48%) thin films on c-plane sapphire substrates have been fabricated by co-sputtering oxidation solutions, and the metal-insulator transition temperature (T ) of Ti V O films rises monotonically at the rate of 1.64 K/at.% Ti. The x-ray diffraction measurement results show that, after Ti ion doping, the rutile structure expands along the c axis while shrinking along the a and b axis simultaneously. It makes the V-O bond length shorter, which is believed to upshift the π orbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Vanadium dioxide (VO 2 ) has attracted a lot of attention due to its significant change in optical and electrical properties [1][2][3][4] during phase transition near room temperature (∼340 K) [1][2][3][4][5][6][7]. Below 340 K, VO 2 is in the monoclinic phase [1][2][3][4][5][6][7][8] (VO 2 (M)) with the space group symmetry P21/c [1,7,8]. In this case it behaves as an insulator with very high resistance * Authors to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vanadium dioxide (VO 2 ) has attracted a lot of attention due to its significant change in optical and electrical properties [1][2][3][4] during phase transition near room temperature (∼340 K) [1][2][3][4][5][6][7]. Below 340 K, VO 2 is in the monoclinic phase [1][2][3][4][5][6][7][8] (VO 2 (M)) with the space group symmetry P21/c [1,7,8]. In this case it behaves as an insulator with very high resistance * Authors to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…value and the thermal conductivity appears at a relatively low value (nearly 3.6 Wm −1 K −1 ) [9]. However, it is shown that when the temperature increases to near 340 K, VO 2 film undergoes a metal-insulator transition [1][2][3][4][5][6][7]; from the monoclinic phase to the rutile phase (VO 2 (R)). As a consequence, above 340 K the film has metal-phase behaviors [1][2][3][4][5][6][7], with low resistance and high thermal conductivity (k ∼ 6.0 Wm −1 K −1 ) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the SMT temperature saturates at 80-85°C as the doping level reaches above about 8at% [37,50]. The previous literature demonstrated the SMT amplitude of Ti- doped VO 2 thin films obviously decreases with Tidoping level, owing to outstanding increase of the resistivity for the metal state [48]. This could originate from stronger Ti-O bonds than V-O ones.…”
Section: High-concentration Ti Was Introduced Intomentioning
confidence: 93%
“…This indicates the existence of monoclinic VO 2 in VTO from RT to 106°C. It has reported that Ti-doping increases the SMT temperature of VO 2 for a low doping level [48,49]. But the SMT temperature saturates at 80-85°C as the doping level reaches above about 8at% [37,50].…”
Section: High-concentration Ti Was Introduced Intomentioning
confidence: 97%